Immunoglobulin G concentration in canine colostrum: Evaluation and variability. (November 2015) - Mila, Hanna; Feugier, Alexandre; Grellet, Aurélien; Anne, Jennifer; Gonnier, Milène; Martin, Maelys; Rossig, Lisa; Chastant-Maillard, Sylvie
Highlights: Variability in immune quality of colostrum among bitches and teats was demonstrated. Neither breed, age of dam or litter size accounted for colostrum immune variability. No single pair of mammary glands produced a secretion of higher immune quality. No difference in IgG concentration was recorded between anterior and posterior pairs. The BRIX index was significantly, but moderately correlated with colostrum IgG concentration. Abstract: Canine neonates are born hypogammaglobulinemic, and colostrum is their main source of immunoglobulins. The purpose of this study was to evaluate the immune quality of canine colostrum and its variability both among bitches and among mammary glands. The immune quality was estimated from immunoglobulin G (IgG) concentration (ELISA test). The correlation of IgG concentration with refractometry was evaluated. From a total of 44 bitches from 13 different breeds from a single breeding kennel, samples of colostrum and blood were collected one day after the parturition onset. Colostrum was collected separately from each pair of mammary glands (180 pairs). The mean colostrum IgG concentration in our population was 20.8 ± 8.1 g/L (ranging from 8.0 to 41.7 g/L) with no influence of breed size, litter size, age of dam or serum IgG concentration. Colostrum IgG concentration varied widely among pairs of mammary glands within one bitch (variation coefficient: 42 ± 32.1%). Nevertheless, no single pair of mammary glands was found to produce regularly a secretion of higher quality. No difference in IgG concentration was recorded between anterior and posterior pairs either. The BRIX index and the refractive index were significantly, but moderately correlated with colostrum IgG concentration ( r  = 0.53 and 0.42, respectively). This study demonstrates a great variability in immune quality of colostrum among bitches and among mammary glands within one bitch. Further studies on the suckling behavior of puppies and on determination of the minimal immune quality of colostrum are required to evaluate their impact of this high variability on neonatal mortality in dogs.